2018
DOI: 10.3126/njes.v6i0.30121
|View full text |Cite
|
Sign up to set email alerts
|

Soil fertility status of agricultural land in mid-hill of Gorkha District, Nepal

Abstract: Soil fertility management in agricultural land is challenging in hilly areas of Nepal. The study assesses the soil fertility status of Bari (upland) and Khet (lowland) agriculture land in Mid-hill of Gorkha district. Altogether 30 samples were collected from soil surface (0 to 20 cm) by using hand shovel in January, 2017. The soil fertility parameters like pH, organic matter (OM), total nitrogen (TN), available phosphorus (P) and available potassium (K) were analyzed using standard methods in the laboratory of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Implementation of conservation practices in a forest will have a direct effect on forest soil (Kiran and Kaur, 2011). Due to changes in topography, vegetation cover, microbial activities, and so on, forest soil differs in time and space (Shrestha et al, 2018).…”
Section: Increase Forest Soil Productivitymentioning
confidence: 99%
“…Implementation of conservation practices in a forest will have a direct effect on forest soil (Kiran and Kaur, 2011). Due to changes in topography, vegetation cover, microbial activities, and so on, forest soil differs in time and space (Shrestha et al, 2018).…”
Section: Increase Forest Soil Productivitymentioning
confidence: 99%
“…Past studied clearly indicated that the fertilizer supplied by the informal sources are of poor quality (Panta, 2018). In this context Shrestha (2018) has remarked:…”
Section: Introductionmentioning
confidence: 99%